(untitled) (MCIT: Proceedings of International scientific and practical conference, 2025)
This document focuses on the optimization of electronic document issuance systems that operate under high user load. As the volume of digital services and e-government platforms increases, the need for faster, more reliable, and scalable document generation becomes crucial. The study investigates key bottlenecks in document processing pipelines and proposes a hybrid approach based on server-side caching and asynchronous task execution. The proposed solution significantly reduces response times and improves the overall throughput of document generation systems. У цьому документі розглянуто оптимізацію систем електронної видачі документів, що працюють під великим навантаженням користувачів. Із зростанням обсягів цифрових сервісів та платформ електронного урядування зростає потреба у швидшому, надійнішому та масштабованішому формуванні документів. У дослідженні проаналізовано основні вузькі місця у процесах обробки документів і запропоновано гібридний підхід, заснований на серверному кешуванні та асинхронному виконанні завдань. Запропоноване рішення суттєво зменшує час відгуку та підвищує загальну пропускну здатність систем генерації документів.